ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI TRANSPORT MEMBRAN SEL DI KELAS XI SMAS PANCA BUDI MEDAN - Ulandari, Sri; Yanti, Sopi; Diana, Putri; Warohmah, Sakinah; Arwita, Widya; Mukra, Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in teaching cell membrane transport material in grade XI at SMAS Panca Budi Medan. This study used a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that PBL was implemented through stages of problem orientation, group discussion, investigation, presentation, and evaluation. This model improved students’ activeness, critical thinking, communication, and collaboration skills. In addition, membrane transport material became easier to understand because it was related to real-life contexts. However, there were obstacles such as limited time and differences in student participation. Overall, the implementation of PBL was effective in improving the quality of biology learning.